Bioactivity of Proplis to the CD4 + and CD8+ T cells Producing IFN-γ Cytokines in BALB / C Mice - Yonna Ayundria; Muhaimin Rifa'i (University of Brawijaya, 2014)
ABSTRACT Propolis (bee glue) is a natural resinous product of honey bees which collected from exudates and plant buds, rich in biochemicals constituents including mostly flavonoids, phenols and various acids bond. These compound are believed to be responsible as immunomodulatory agents. The study aims to determine the immunomodulatory activity of ethanolic extract of propolis to the CD4+ and CD8+ T cells producing IFN-γ cytokines and analyze the differences immune responses between control and treatment group by in vivo. Stages include animal acclimation for ± 1 week, preparation of Ethanolic Extracts of Propolis / EEP, Oral Administration with doses levels of 0 mg / kg BW; 50 mg / kg BW (DI); 100 mg / kg BW( DII); 200 mg / kg BW (DIII) for 2 weeks, isolation of lymphocyte cells from spleen, flowcytometry analysis to asses cell number and surface molecule expression. Data was analyzed using Kruskal Wallis Test with α = 0,05 and followed by Mann Whitney Test by SPSS 16.0 for windows with complete randomized design. The results showed that a dose of 50 mg / kg BW was increases the relative number of CD8+ T cells producing IFN-γ cytokines significantly (p <0.05) compared with controls. However, at the same dose the relative number of CD4+ T cells producing IFN-γ cytokines was decreased significantly (p<0,05). Based on this case, its dose supposedly that the ethanolic extract of propolis play role in maintaining the balance or homeostatic of IFN-γ cytokines production by T cell subsets. Dose of 100 mg/kg BW and 200 mg / kg BW could decrease the relative number of activated CD4+ T cells producing IFN-γ cytokine significantly compared to controls. Keywords: CD4+ T cells, CD8+ T cells, ethanolic extract of propolis, IFN-γ cytokines, in vivo